2004
DOI: 10.1159/000083471
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Audit of the Complications of Loop Ileostomy Construction and Takedown

Abstract: Aim: A prospective review of the complications of ileostomy construction and takedown. Materials and Methods: One hundred twenty-seven consecutive patients undergoing construction of a loop ileostomy were included in a prospective nonrandomized computer database. Complications of the loop ileostomy were assessed prior to and after closure. Three closure techniques were performed [enterotomy suture (25.7%), resection and hand sewn (31.2%) or stapled anastomosis (43.1%)] and compared. Results: One hundred twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
103
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 51 publications
6
103
0
Order By: Relevance
“…Reported incidence of dehydration ranges from 2.2-20% [19]. These patients have to be on a stringent diet and anti-diarrheal medication often [20]. Some recommend such measures only if urinary sodium concentration is low (0-10 meq/L), and delay discharge till effluent is less than 1 L/day.…”
Section: Discussionmentioning
confidence: 99%
“…Reported incidence of dehydration ranges from 2.2-20% [19]. These patients have to be on a stringent diet and anti-diarrheal medication often [20]. Some recommend such measures only if urinary sodium concentration is low (0-10 meq/L), and delay discharge till effluent is less than 1 L/day.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective review of the complications of ileostomy closure reported an SSI rate of 18.3% (9). The high incidence rate of SSI was considered to be associated with the primary closure of these wounds.…”
Section: Discussionmentioning
confidence: 99%
“…However, diverting loop‐ileostomy potentially increases the risks for stoma‐related complications including small bowel obstruction (SBO), stoma prolapse, stoma retraction, parastomal hernia, parastomal dermatitis, and mucocutaneous dehiscence. Risks for stoma‐related complications are reportedly 5‐46% 6, 7, 8, 9…”
Section: Introductionmentioning
confidence: 99%